2011
DOI: 10.20867/thm.17.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The research results of charter companies in Croatia

Abstract: Demand for Croatia as a nautical country constantly maintains the upward trend. The reason for this is the fact that Croatia is on the way to the EU integration as a future equal member state. This fact significantly contributes to Croatia’s openness to the generating market in both economical and in terms of tourism. Nautical tourism of Croatia is profitable which has been recognized by foreign entrepreneurs by directing their fleets to the Adriatic and developing successful and today frequently leading chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…The importance of digital services in the yacht charter segment is evidenced by previous work [47,49,50] showing that advertising on the Internet is the most important form of advertising for charters in nautical tourism, with a share of over 50%, indicating the importance of digital channels and indirectly digital business models for charter activities in nautical tourism. In Kalči's [50] study, most participants indicated that they prefer to book a yacht charter over the Internet rather than via telephone or face-to-face contact.…”
Section: Specifics Of Yacht Charter Accommodationmentioning
confidence: 87%
See 1 more Smart Citation
“…The importance of digital services in the yacht charter segment is evidenced by previous work [47,49,50] showing that advertising on the Internet is the most important form of advertising for charters in nautical tourism, with a share of over 50%, indicating the importance of digital channels and indirectly digital business models for charter activities in nautical tourism. In Kalči's [50] study, most participants indicated that they prefer to book a yacht charter over the Internet rather than via telephone or face-to-face contact.…”
Section: Specifics Of Yacht Charter Accommodationmentioning
confidence: 87%
“…Operationally, yacht charter activity is carried out by specialized charter companies. From the work of Gračan et al [47], it is clear that a charter company is essentially a company that carries out the activity of renting yachts, where it can rent its own yachts or the yachts of others on the basis of a charter management contract. The specificity of charter companies is that they form and maintain fleets of vessels and commercially manage these fleets, including their technical maintenance and commercial use of their capacities.…”
Section: Specifics Of Yacht Charter Accommodationmentioning
confidence: 99%
“…Sailors visiting ports constitute a great purchasing power and generate demand for various services, thus stimulating the development of local entrepreneurship [15]. Charter services are treated in some countries, such as Croatia, as a key element of the tourism economy [16]. During a pandemic, however, it is important to note that the specificity of sailing tourism may make it resistant to many limitations of the situation.…”
Section: Introductionmentioning
confidence: 99%